Febrile convulsions and sudden infant death syndrome. Issue 2 (1st February 2002) - Vestergaard, M; Basso, O; Henriksen, T B; Østergaard, J; Olsen, J
Abstract : It has been suggested that sudden infant death syndrome (SIDS) and febrile convulsions are related aetiologically. We compared the risk of SIDS in 9877 siblings of children who had had febrile convulsions with that of 20 177 siblings of children who had never had febrile convulsions. We found no support for the shared susceptibility hypothesis.